Data of the project "Salt efflorescence on leather objects from the Vasa ship - Part I" (project number RAÄ-2019-2239) - Sandström, Johanna; Öhrström, Lars; Mystere Amombo Noa, Francoise; Hacke, Marei; Berg, Helena (Swedish National Heritage Board, 2024)
Data from the project "Salt efflorescence on leather objects from the Vasa ship - Part I". Reports from the following analytical techniques is included together with instrument data:

Scanning electron microscopy with energy dispersive x-ray spectroscopy (SEM-EDS);

X-ray fluorescence spectroscopy (XRF);

FTIR spectroscopy

Raman spectroscopy

Data colledted at the Swedish National Heritage Board (www.raa.se). Project number Dnr RAÄ-2019-2239.

Objects from the Vasa ship:

http://kulturarvsdata.se/smm-vm/photo/Fo173041dig
Keywords: Heritage Science; Vasa ship; Salt efflorescence; leather; PEG-treated; RAÄ-2019-2239; waterlogged; organic material; Shipwreck; archaeological objects; archaeological conservation; polyethylene glycol; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi